Bronasti jezdec Puškina in Leto tisoč devetsto trinajst Ahmatove - Podlesnik, Blaž (Slavistična revija, 2000)
The article is devoted to the comparison of the "St. Peterburg stories" by Pushkin and Akhmatova with the intention of shedding light on the common features and differences on the style of verse narrative. It also attemps to outline the way Akhmatova in the spirit of modernism transforms some traditional narrative formulas. Despite the common thematic features (an individual and the city of Petersburg) Akhmatova's verse narrative differs from the tradition of Pushkin mainly by its new narrative position (distances poetic "self" losing his integrity), a text without a sujet, and the dominant role of the lyrical, subjective elements.
Keywords: Ahmatova, Anna Andrejevna; Ahmatova, Anna Andrejevna: Leto tisoč devetsto trinajst; literarne študije; Puškin, Aleksandr Sergeevič; Puškin, Aleksandr Sergeevič: Bronasti jezdec; Puškin, Aleksandr Sergeevič: Mednyj vsadnik; ruska književnost; ruska poezija